Kekuatan Hukum Keterangan Seseorang Justice Collaborator Dalam Perkara Tindak Pidana Korupsi - Anugraha, Fahmi; Ismail, Ismail (Legalitas: Jurnal Hukum, 2024)
Corruption crimes both directly and indirectly can harm state finances or the state economy while at the same time also harming the people. This is based on Law of the Republic of Indonesia Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Commission for the Eradication of Corruption Crimes in Paragraph 1 Number 4 which regulates that the eradication of Corruption Crimes is a series of activities to prevent and eradicate the occurrence of criminal acts. corruption through efforts to coordinate, supervise, monitor, investigate, investigate, prosecute, examine in court, with community participation in accordance with statutory provisions. The legal research method used is normative, supported by court decisions, with data collection by means of documentation studies, literature studies and interviews. The statement of a person who has the status of a Justice Collaborator in a criminal corruption case has significant legal force, but also requires careful evaluation by the court as a whole. The Justice Collaborator's statement has important legal force in the judicial process, but the final decision still depends on a thorough evaluation. by the court and the clarity and reliability of the information provided.